Endless modernisation: Power and knowledge in the Green Morocco Plan. (March 2023) - Mathez, Andrea; Loftus, Alex
In 2008, in the aftermath of the World Food Crisis and in a context of an unfolding New Green Revolution for Africa, Morocco launched the Green Morocco Plan to 'modernise' its agricultural sector, thereby making the latter the main driver for economic growth and for the alleviation of rural poverty. Yet, the technicist-productivist rationale of the Green Morocco Plan, characteristic of New Green Revolution modernisation schemes, renders any positive socio-ecological outcome unlikely. Hence, recent studies of the Green Morocco Plan have focused on its impacts on food security, inequality and environment. However, how the Green Morocco Plan's rationale is (re)produced within a given set of socio-ecological, material relations has to date attracted relatively little attention. This study, therefore, explores the power-knowledge dynamics of the modernisation discourse within the Green Morocco Plan as a driver of socio-ecological change. Bringing together insights from political ecology, critical development and agri-food studies, we show how the entangled set of ideological, material, political and technical processes embodied within the Green Morocco Plan favours a reductionist view of agricultural development as increasing yields and profits. In so doing, such a view perpetuates efforts to 'modernise' smallholder/family farming.